Holoptelea integrifolia bark and leaves phytochemicals, an effective ethno-pharmacological remedy for treating oral- dental infections (Funded Work) - Karuna Sharma; Sanjay Chhibber; Kusum Harjai (International Journal of Pharma and Bio Sciences, 2020)
Holoptelea integrifolia (Ulmaceae) is a versatile medicinal plant encompassing a wide range of pharmacological properties. The present study is aimed at assessment of anti-bacterial activities of bark and leaf phytochemicals against the common oral bacterial pathogens namely Staphylococcus aureus, Streptococcus oralis, Streptococcus mutans, Streptococcus gordonii, Lactobacillus brevis and Lactobacillus casei. Bark and leaf dried powder samples were Soxhlet fractionated with solvents viz. petroleum-ether, chloroform, absolute-ethanol, 80%-methanol and distilled-water. Antibacterial potentials of the fractionated extracts against oral pathogens were evaluated with respect to zone of inhibition, MIC, MBC and IC50 values whereas antioxidant activities were assessed against ABTS+ and DPPH free radicals. The results demonstrated significantly higher antibacterial activity in bark ethanolic extracts (HiBE) towards every tested oral bacterial pathogen as established by its greater zone of inhibition and lowest MIC, MBC and IC50 values. HiBE most potent antibacterial action against L. casei followed by L. brevis, S. mutans, S. aureus, S. gordonii and S. oralis HiBE showed remarkable ABTS+ and DPPH free radicals scavenging activities with abundance of phenolics, flavanoids and tannins. Therefore, the present study ascertains H. integrifolia bark extracts as a commendable natural remedy for treating oral-dental infections.